(untitled) (Italian Review of Legal History, 2020)
The Project of a great new Public Library in Milano (Biblioteca europea di informazione e cultura, Beic), should be endowed, inter alia, with the works of about 1000 classic Authors of the European and world of the literature, sciences, mathematics, religions, philosophy, history, economy, natural history, biology, law, music, painting, and other subjects on open shelves. The Beic Project is now in stand by, but an area in Milan is still reserved to it and the architectural Project by Peter Wilson has been completed. The buiding, if financed, could start soon. The Fondazione Beic - chaired by Antonio Padoa-Schioppa from its start in 2004 to 2017 and now chaired by dr. Francesco Tronca, former praefect of Milano - has devoted the last twelve years to build a Digital library (BeicDL) that includes at present 20 Collections in different areas; among them History, European Literatures, Mathematics, Medicine, Italian Incunabola, Italian Academies’ publications, Law, Economy, Idraulics, Journeys in Italy and Europe; sofar, about 100.000 records and 30.000 volumes. The Law Collection of BeicDL, still open to further development, is particulary rich, as it includes at present 1488 printed books of European ius commune (sec. XII-XVIII), 280 legal incunables, 2481 medieval legal manuscripts from microfilms of 240 European libraries, all owned by the Law Library of the Università di Milano, several hundreds of Italian medieval and early modern communal Statutes and of medieval documents and chronicles, among them the whole series of the Fonti per la Storia d’Italia (see Appendix VI of this paper). All the documents of BeicDL are freely available online (www.beic.it).